Issues of Inequality and the Political Economy in the 1990s Singapore: A Marxist Reading on Alfian bin Sa’at’s “Birthday” - Bima Iqbal Khadafi (Journal of Language and Literature, 2022)
This research closely reads a short story by Alfian bin Sa’at entitled “Birthday” in relation to the historical narrative and the political economy of 1990s Singapore using the perspective of Terry Eagleton’s Marxist literary criticism. The result of this study shows 1) that Alfian challenges a portion of the historical narrative of Singapore’s political economy in the 1990s at which ideology works to justify the power hierarchy, yet altogether highlights the other portion of it to shed some light on the oppressed; 2) that challenging and, at the same time, highlighting the historical narrative are Alfian’s strategy to endorse his political commitment while not being openly partisan; and 3) that Alfian carefully configures the literary form and content of his work – through his use of multilingualism and Singaporean English – to advocate his idea of the future of Singapore and – through his use of simple sentences that build a stream-of-consciousness plot – to underline the complex social realities whereby issues of inequality (gender, racial, and class) are correlated. This study implies that the use of Marxist literary criticism in reading a literary work from a formerly colonized country cannot neglect the traces of neo- and/or colonial experiences since colonialism itself, following Marx and postcolonial theorists, is a more acute form of capitalism. However, this paper finds that, different from the usual postcolonial reading, the Singaporeans (its capitalists and government) are as complicit as the Western neo-colonial enterprises for the inequalities and oppression happening in the region.